THE USE OF TED TALKS VIDEOS AS LEARNING MATERIALS IN AN INTERMEDIATE LISTENING CLASS IN A PRIVATE UNIVERSITY IN YOGYAKARTA - Upa, Yunika; Muljiani, Retno (English Education Department, 2023)
Listening has a crucial role in developing communication skills in English as Foreign Language (EFL) context. Facilitating EFL listening activities can be conducted by using various resources such as online video providers, interactive websites, and web-based podcasts.TED Talk is one of the online video series that can be used for undergraduate students to develop their listening comprehension in learning EFL. This study aimed to investigate the use of TED Talk videos in developing EFL listening comprehension and the benefits of listening to TED Talk videos. The study was conducted in an Intermediate Listening Class at a Private University in Yogyakarta. The research subjects were 27 students. The researchers collected data by distributing questionnaires and conducting in-depth interviews with the students. Purpose sampling was employed to result in 3 students. Four students with the highest and lowest results were chosen to be examined thoroughly. The result showed that TED Talk videos helped to develop EFL listening comprehension even though not significant. Listening to TED Talk videos can also motivate undergraduate students to learn English, and can enrich the students’ general knowledge.